An assessment of community involvement in cultural heritage of Baba Nyonya culture in Jalan Tun Tan Cheng Lock and Jalann Hang Jebat, Melaka - Kamal, Anis Sofea; Bachok, Syahriah; Mohamed Osman, Mariana; Ibrahim, Mansor (IIUM Press, 2015)
The study is to assess the level of community involvement in cultural heritage of Baba-Nyonya community in Melaka